2015
DOI: 10.1039/c4gc02483d
|View full text |Cite
|
Sign up to set email alerts
|

Bio-derived materials as a green route for precious & critical metal recovery and re-use

Abstract: Overview of research in critical and precious metal recovery using biosorption, application to real-life wastes and uses of the metal-loaded materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
123
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(133 citation statements)
references
References 196 publications
(75 reference statements)
0
123
0
Order By: Relevance
“…It is defined as the property of certain biomolecules or types of biomass (biosorbents), to bind and concentrate selected ions or molecules from aqueous solutions by a metabolically-passive process [5]. The mechanisms of biosorption are generally based on physicochemical interactions between adsorbates and the functional groups present on the biomass surface, such as electrostatic interactions, ion exchange, metal ion chelation or complexation [6]. In the last years, biosorption on marine seaweeds, agricultural wastes, forest residues and industrial byproducts, in native or modified forms, have been indicated as promising technologies for the uptake of heavy metals and organic contaminants from waters [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as the property of certain biomolecules or types of biomass (biosorbents), to bind and concentrate selected ions or molecules from aqueous solutions by a metabolically-passive process [5]. The mechanisms of biosorption are generally based on physicochemical interactions between adsorbates and the functional groups present on the biomass surface, such as electrostatic interactions, ion exchange, metal ion chelation or complexation [6]. In the last years, biosorption on marine seaweeds, agricultural wastes, forest residues and industrial byproducts, in native or modified forms, have been indicated as promising technologies for the uptake of heavy metals and organic contaminants from waters [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Because of global modernization and industrialization, pollution caused by the release of heavy metals into the environment has become a critical issue, and thus concerns surrounding the recovery of such heavy metals have been rising (Dodson et al 2015). Among all metals commonly seen in wastes, gold is a noble metal and can be used in luxury jewelry, electronics, and medical applications because of its unique physical and chemical properties such as high biocompatibility and long-term stability (Ramesh et al 2008;Spitzer and Bertazzoli 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of adsorbed Cd(II) ions per gram wheat bran at equilibrium, qe (mg/g), and the removal percentage, (% A), were calculated using the following equations: %A = C 0 −C e / C 0 × 100 (1) q e = (C 0 −C e )V/m (2) …where C 0 and C e are the initial and equilibrium concentrations of Cd(II), respectively (mg/dm examined by an FTIR spectrophotometer (Shimadzu, FTIR 8400 S with KBr disc). The retentate of biosorbent pretreatment was subjected to heterogeneous (cellulose acetate-coal) asymmetric reverse osmosis membranes (batch 317).…”
Section: Methodsmentioning
confidence: 99%
“…Several conventional methods (e.g., chemical precipitation, coagulation, sedimentation, adsorption, reduction, oxidation, solvent extraction, electrolytic extraction, evaporation, ion exchange, dialysis/electrodialysis, membrane processes, etc.) have been used to achieve effective and rapid removal of these environmental contaminants -particularly metal ions because of their toxic nature and high production cost, and limited or decreasing availability of metal deposits [1][2].…”
mentioning
confidence: 99%